1998
DOI: 10.1073/pnas.95.22.13091
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of caloric restriction in Caenorhabditis elegans

Abstract: Low caloric intake (caloric restriction) can lengthen the life span of a wide range of animals and possibly even of humans. To understand better how caloric restriction lengthens life span, we used genetic methods and criteria to investigate its mechanism of action in the nematode Caenorhabditis elegans. Mutations in many genes (eat genes) result in partial starvation of the worm by disrupting the function of the pharynx, the feeding organ. We found that most eat mutations significantly lengthen life span (by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
762
5
16

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 881 publications
(821 citation statements)
references
References 44 publications
38
762
5
16
Order By: Relevance
“…As NP1 did not appear to decrease feeding rate in vivo and did not cause worms to appear starved or poorly fed, we thought it unlikely that the NP1 pumping rate defect could cause such a profound increase in lifespan. Genetic mutations that result in DR from mechanical impairments of feeding are well known in C. elegans (Lakowski & Hekimi, 1998). EAT‐2 is an acetylcholine receptor subunit responsible for promoting the rapid pumping of pharyngeal muscle (Raizen et al ., 1995; McKay et al ., 2004).…”
Section: Resultsmentioning
confidence: 99%
“…As NP1 did not appear to decrease feeding rate in vivo and did not cause worms to appear starved or poorly fed, we thought it unlikely that the NP1 pumping rate defect could cause such a profound increase in lifespan. Genetic mutations that result in DR from mechanical impairments of feeding are well known in C. elegans (Lakowski & Hekimi, 1998). EAT‐2 is an acetylcholine receptor subunit responsible for promoting the rapid pumping of pharyngeal muscle (Raizen et al ., 1995; McKay et al ., 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Dauer-formation is not considered a model for the mammalian CR response, and mechanisms regulating dauer formation appear to be independent of those regulating response to standard C. elegans CR treatments (applied during the adult stage) (Lakowski and Hekimi 1998). However, since dauer formation represents a metabolic response to resource limitation that is accompanied by increased longevity, it was suspected that dauerregulated genes could share some network properties with CR-regulated genes.…”
Section: Invertebrate Models Of Crmentioning
confidence: 99%
“…To determine if there is a single pathway by which senescence is retarded, we have examined four separate manipulations that have been shown to increase lifespan in C. elegans: dietary restriction (DR), cold-/hypothermic-induced longevity (CHIL), decreased insulin signaling, and mutations influencing mitochondrial respiration (Ball et al 1947;Conti et alDietary restriction has been shown to extend lifespan by up to 50% in mammals (Davis et al 1983;Yu et al 1985;Weindruch and Walford 1982). In several different worm models of dietary restriction, evidence has revealed that DAF-16, a forkhead box O (FOXO) transcription factor that is required for lifeextension via the insulin pathway, is not required for the life-extending effects of dietary restriction (Houthoofd et al 2003;Lakowski and Hekimi 1998). This observation suggests, contrary to the overwhelmingly compelling hypothesis, that the insulin-like pathway does not mediate the effects of dietary restriction.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which clk-1 extends lifespan is controversial. Studies have both shown that clk-1 does and does not extend lifespan when the worms undergo dietary restriction (Braeckman et al 2000;Lakowski and Hekimi 1998). This difference may be explained by the difference in application of caloric restriction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation